PERAN TOKOH ELIS DAN KONFLIK SOSIAL DALAM NOVEL ELIS TANDIGO KARYA ERLINA MAMUS - Gosa, Nastiana; Purnamasari, Hetty; Amrullah, Imron (Transpublika Publisher, 2023)
The problems discussed in this study are (1) How is the role of Elis character in the novel Elis Tandigo by Erlina Mamus? (2) How is the internal conflict in the novel Elis Tandigo by Erlina Mamus? (3) How is the external conflict in the novel Elis Tandigo by Erlina Mamus?. The purpose of this study is to describe: (1) the role of Elis character in Elis Tandigo novel by Erlina Mamus (2) internal conflict in Elis Tandigo novel by Erlina Mamus (3) External conflict in Elis Tandigo novel by Erlina Mamus. In conducting this research, the method used is descriptive qualitative method. The main data source in this research comes from the novel Elis Tandigo by Erlina Mamus. Data collection in this research uses literature study technique by reading and understanding the novel. The data analysis technique uses a flowing analysis technique which includes data reduction, data presentation, and conclusion drawing. Based on the research conducted, it is concluded that this novel tells the story of Elis who plays a very important role because she is often the person in solving problems or solving problems in society.